Contesting Islamic Educational Values: A Minangkabau Response to Indonesia’s National Hijab Policy - Wedra Aprison; Abdulramae Sulong; Afrinaldi Afrinaldi; Ismail Ismail; Irwandi Irwandi (Jurnal Pendidikan Islam, 2025)
Indonesia’s Joint Ministerial Decree (SKB Tiga Menteri), which prohibits schools from mandating the hijab, has sparked significant controversy, particularly in Minangkabau society, where Islamic norms are strongly interwoven with adat and educational traditions. This study aims to analyze the roots of Minangkabau resistance to the hijab policy and to understand what this conflict reveals about broader negotiations between state authority and local Islamic educational values. Employing a qualitative fieldwork approach, the research integrates in-depth interviews, field observations, and digital documentation. These primary data are complemented by qualitative content analysis of media reports, public statements, and community narratives to capture both grassroots and public discourses. Findings show that Minangkabau communities interpret the policy as undermining the moral development of children and disrupting the long-standing normalization of hijab practice in schools. Their resistance signifies a strong assertion of educational autonomy and reflects a challenge to the state’s attempt to centralize religious policy. This contestation is rooted not only in religious doctrine but also in cultural heritage and communal identity. The Minangkabau reaction highlights the persistent dissonance between national education policies and local religious-cultural frameworks, demonstrating that uniform regulations may fail to accommodate Indonesia’s plural sociocultural landscape. The study underscores the need for culturally responsive policy-making in Islamic education, encouraging future decisions to integrate local values, community participation, and context-sensitive approaches to avoid conflict and strengthen policy legitimacy.